Positive electrode for rechargeable lithium battery and rechargeable lithium battery including same
By using the dry positive electrode active material layer of large and small particles of lithium iron phosphate particles and polytetrafluoroethylene binder in the dry process, the problem of poor adhesion of the positive electrode active material layer of the dry battery is solved, and a positive electrode with high energy density and high load level is achieved.
Patent Information
- Application Number
- CN202410638009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-05-22
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to prepare a positive electrode of a rechargeable lithium battery with high energy density in a dry process, and the positive electrode active material layer of the dry battery has poor adhesion on the current collector, resulting in uneven coating.
A dry positive electrode active material layer containing large and small particles of lithium iron phosphate particles and polytetrafluoroethylene binder was used to eliminate solvents through the dry mixing process to prepare a positive electrode with high energy density.
It is realized that positive electrodes with high energy density are prepared in the dry process, the load level and current density are improved, and the uniformity and adhesion of the positive electrode active material layer are ensured.
Smart Images

Figure CN119725390A_ABST
Abstract
Description
Technical Field
[0001] According to one or more embodiments, the present disclosure relates to a positive electrode for a rechargeable lithium battery and a rechargeable lithium battery including the positive electrode. Background Art
[0002] In order to achieve relatively high performance of one or more suitable devices (e.g., consumer electronic devices), it is becoming increasingly important for rechargeable batteries to have relatively high energy density (or battery energy density). For example, rechargeable lithium batteries with suitable discharge voltage and relatively high energy density are becoming increasingly important or desirable.
[0003] Electrodes for rechargeable lithium batteries can be prepared by using a wet process or a dry process. Therefore, further research on the dry process, which is a relatively simple process that can impart higher capacity, is desired. Summary of the invention
[0004] One or more aspects relate to a positive electrode for a rechargeable lithium battery exhibiting high energy density.
[0005] One or more aspects relate to a rechargeable lithium battery including a positive electrode.
[0006] One or more aspects relate to a positive electrode for a rechargeable lithium battery, the positive electrode including a dry positive active material layer including a positive active material of large and small lithium iron phosphate particles and a polytetrafluoroethylene binder.
[0007] One or more aspects relate to a rechargeable lithium battery including a positive electrode, a negative electrode, and a non-aqueous electrolyte.
[0008] Additional aspects are included in the detailed description which follows, and in part will be apparent from the description, or may be learned by practice of the disclosed presented embodiments.
[0009] A positive electrode for a rechargeable lithium battery according to one or more embodiments may exhibit relatively high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 A partial cross-sectional view of a rechargeable lithium battery as a cylindrical battery according to one or more embodiments of the present disclosure is shown.
[0011] Figure 2 A cross-sectional view of a rechargeable lithium battery as a prismatic battery according to one or more embodiments of the present disclosure is shown.
[0012] Figure 3 A rechargeable lithium battery as a pouch type or bag-like battery according to one or more embodiments of the present disclosure is shown.
[0013] Figure 4 An exploded view of a rechargeable lithium battery as a pouch-type or bag-like battery according to one or more other embodiments of the present disclosure is shown. DETAILED DESCRIPTION
[0014] By referring to the detailed description and drawings of the embodiments, it is easier to understand the aspects of some embodiments of the present disclosure and the methods for realizing them. The described embodiments are provided as examples so that the present disclosure will be thorough and complete, and will fully convey the aspects of the present disclosure to those skilled in the art. Therefore, redundant, irrelevant or unrelated to the description of the embodiments, or processes, elements and techniques that are not necessary for a person of ordinary skill in the art to fully understand the aspects of the present disclosure may not be provided. Unless otherwise indicated, the same reference numerals, characters or combinations thereof always represent the same elements, and their repeated descriptions may not be provided in the drawings and written descriptions.
[0015] The described embodiments may have one or more suitable modifications and may be embodied in different forms and should not be construed as being limited to the embodiments shown here. When describing some embodiments, the use of "may", "may" or "may not" corresponds to one or more embodiments of the present disclosure. The present disclosure covers all modifications, equivalents and replacements within the conceptual and technical scope of the present disclosure. In addition, each of the features of one or more suitable embodiments of the present disclosure may be partially or completely combined with each other, and one or more suitable interlocks and drives are technically possible. Each embodiment may be implemented independently of one another, or may be implemented together in association.
[0016] In the drawings, the relative sizes of elements, layers, and regions may be exaggerated for clarity and / or descriptive purposes. In addition, the use of cross-hatching and / or shading in the drawings is generally provided to clarify the boundaries between adjacent elements. As such, unless otherwise stated, the presence or absence of cross-hatching or shading does not convey or indicate any preference or requirement for a particular material, material property, size, ratio, commonality between the elements shown, and / or any other characteristic, attribute, property, etc. of an element.
[0017] Various embodiments are described herein with reference to cross-sectional views as schematic diagrams of embodiments and / or intermediate structures. Therefore, variations in the illustrated shapes due to, for example, manufacturing techniques and / or tolerances are expected. In addition, for the purpose of describing embodiments according to the concepts of the present disclosure, the specific structures or functional descriptions disclosed herein are merely illustrative. Therefore, the embodiments disclosed herein should not be interpreted as being limited to the illustrated shapes of elements, layers, or regions, but include shape deviations caused by, for example, manufacturing.
[0018] In the accompanying drawings, for the sake of clarity, the thickness of the layers and regions is exaggerated or reduced. For ease of explanation, spatial relative terms such as "under ... ", "under ... ", "underside", "under ... ", "above ... ", "on ", "upper side", etc. can be used here to describe the relationship between an element or feature and another (some) element or feature as shown in the drawings. It will be understood that, in addition to the orientation depicted in the drawings, the spatial relative terms are intended to cover the different orientations of the device in use or operation. For example, if the device in the drawings is turned over (for example, when the device in the drawings is turned over), the elements described as "under" other elements or features, "under" or "below" will then be oriented to "above" the other elements or features. Therefore, the example terms "under ... " and "under ... " can cover both the upper orientation and the lower orientation (for example, the upper orientation and the lower orientation at the same time). The device can be oriented in addition (for example, rotated 90 degrees or in other orientations), and the spatial relative descriptors used here should be interpreted accordingly. Similarly, if a first part is described as being arranged “on” a second part (for example, when the first part is described as being arranged “on” a second part), this means that the first part is arranged at the upper side or lower side of the second part (not limited to its upper side) based on the direction of gravity.
[0019] It will be understood that if an element, layer, region, or component is referred to as being "formed on," "on," "connected to," or "(operably or communicatively) coupled to" another element, layer, region, or component (for example, when an element, layer, region, or component is referred to as being "formed on," "on," "connected to," or "(operably or communicatively) coupled to" another element, layer, region, or component), it may be directly formed on, directly on, directly connected to, or directly coupled to the other element, layer, region, or component, or indirectly formed on, indirectly on, indirectly connected to, or indirectly coupled to the other element, layer, region, or component, such that one or more intervening elements, layers, regions, or components may be present. In some embodiments, this may be collectively referred to as direct or indirect coupling or connection and integral or non-integrated coupling or connection. For example, if a layer, region, or component is referred to as being "electrically connected" or "electrically coupled" to another layer, region, or component (e.g., when a layer, region, or component is referred to as being "electrically connected" or "electrically coupled" to another layer, region, or component), it may be directly electrically connected or directly electrically coupled to the other layer, region, and / or component, or there may be one or more intervening layers, regions, or components. The one or more intervening components may include switches, resistors, capacitors, etc. When describing embodiments, unless explicitly described as being directly connected, the statement of connection indicates an electrical connection, and "directly connected / directly coupled" or "directly on..." means that one component is directly connected or directly coupled to another component, or is directly on another component, without intervening components.
[0020] In some embodiments, in this specification, if a part of a layer, film, region, plate, etc. is formed on another part (for example, when a part of a layer, film, region, plate, etc. is formed on another part), the formation direction is not limited to the upper direction, but includes forming the part on the side surface or in the lower direction. On the contrary, if a part of a layer, film, region, plate, etc. is formed "below" another part (for example, when a part of a layer, film, region, plate, etc. is formed "below" another part), this not only includes the case where the part is "directly under" the other part, but also includes the case where there is another part between the part and the other part. In some embodiments, other expressions describing the relationship between components, such as "between...", "directly between..." or "adjacent to..." and "directly adjacent to..." can be similarly interpreted. It will be understood that if an element or layer is referred to as "between" two elements or layers (for example, when an element or layer is referred to as "between" two elements or layers), it can be the only element or layer between the two elements or layers, or one or more intermediate elements or layers may also exist.
[0021] For the purpose of this disclosure, if a statement such as “at least one of…” or “any one of…” or “one or more of…” or “selected from…” precedes or follows a list of elements (for example, when a statement such as “at least one of…” or “any one of…” or “one or more of…” or “selected from…” precedes or follows a list of elements), the entire list of elements is modified without modifying the individual elements of the list. For example, “at least one of X, Y, and Z”, and “at least one selected from the group consisting of X, Y, and Z” may be interpreted as only X, only Y, only Z, any combination of two or more of X, Y, and Z (such as XYZ, XY, YZ, and XZ for example), or any variation thereof. Similarly, the statement “at least one of A and B” may include A, B, or A and B. As used herein, "or" generally refers to "and / or", and the term "and / or" includes any and all combinations of one or more of the relevant listed items. For example, the expression "A and / or B" may include A, B, or A and B. Similarly, if expressions such as "at least one of", "multiple", "one of" and other prepositional phrases precede or follow a list of elements (for example, when expressions such as "at least one of", "multiple", "one of" and other prepositional phrases precede or follow a list of elements), the entire list of elements is modified without modifying the individual elements of the list. Here, "or" should not be interpreted as an exclusive meaning, for example, "A or B" is interpreted as including A, B, A+B, etc.
[0022] It will be understood that, although the terms "first", "second", "third" etc. can be used here to describe one or more suitable elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms do not correspond to a specific order, position or priority, and are only used to distinguish an element, member, component, region, area, layer, section or part from another element, member, component, region, area, layer, section or part. Therefore, without departing from the spirit and scope of the present disclosure, the first element, component, region, layer or part can be referred to as the second element, component, region, layer or part. Describing an element as a "first" element may not require or imply the presence of a second element or other elements. The terms "first", "second" etc. can also be used here to distinguish elements of different categories or groups. For simplicity, the terms "first", "second" etc. can respectively represent "first category (or first group)", "second category (or second group)" etc.
[0023] The term used herein is only used for the purpose of describing the embodiment, and is not intended to limit the present disclosure. As used herein, unless the context clearly indicates otherwise, the singular form "one" and "one (kind / person)" are also intended to include plural forms, and the plural form is also intended to include singular forms. It will also be understood that if the term "include", "comprise", "have" and its variants are used in this specification (for example, when the term "include", "comprise", "have" and its variants are used in this specification), it is explained that there are stated features, integral bodies, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integral bodies, steps, operations, elements, components and / or their groups. The term "combination thereof" can include a mixture, laminate, composite, copolymer, alloy, blend, reactant of a component.
[0024] As used herein, the terms "substantially", "about", "approximately" and similar terms are used as approximate terms rather than as terms of degree, and are intended to explain the inherent deviations of measured or calculated values that will be recognized by those of ordinary skill in the art. For example, "substantially" may include a range of + / -5% of the corresponding value. Taking into account the measurement discussed and the errors associated with the measurement of a specific amount (i.e., the limitations of the measurement system), as used herein, "about" or "approximately" includes the stated value and refers to the acceptable deviation range of the specific value as determined by those of ordinary skill in the art. For example, "approximately" may refer to within one or more standard deviations, or within ±30%, ±20%, ±10%, ±5% of the stated value. In addition, if an embodiment of the present disclosure is described (e.g., when describing an embodiment of the present disclosure), the use of "may" refers to "one or more embodiments of the present disclosure".
[0025] The term "combination thereof" may include mixtures, laminates, composites, copolymers, alloys, blends, reactants of the components.
[0026] In some embodiments herein, if viewed from a plan view (eg, when viewed from a plan view), a “layer” includes a shape formed entirely on an entire surface or a shape formed on a portion of a surface.
[0027] Unless otherwise defined, all terms used herein (including chemical terms, technical terms and scientific terms) have the same meaning as those commonly understood by those of ordinary skill in the art to which the present disclosure belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and / or this specification, and should not be interpreted in an idealized or overly formal sense, unless explicitly defined as such herein.
[0028] Unless otherwise defined in the specification, particle diameter or size can be average particle diameter. Average particle diameter represents the average particle diameter (D50) when the cumulative volume is about 50 volume % in the particle size distribution. Particle size (D50) can be measured, for example, by a particle size analyzer or by a transmission electron microscope image or a scanning electron microscope image. In certain embodiments, a dynamic light scattering measurement device is used to perform data analysis, and the number of particles of each size range is counted, so that the average particle diameter (D50) value can be easily obtained by calculation. In addition, according to the context, when the particle is spherical, "diameter" represents particle diameter or average particle diameter, and when the particle is non-spherical, "diameter" represents major axis length or average major axis length. As used herein, the term "fibrillation" or its variant refers to one or more discrete individual units of a material, which is smaller than the fiber of the material. As used herein, the term "fibrillation" and its variant refer to (for example, by grinding or pulverizing) the process of converting the fiber of a material into an individual unit (i.e., fibrillation) of the material smaller than the fiber.
[0029] In this article, "essentially consisting of..." means that any additional component will not have a significant effect on the chemical, physical, optical or electrical properties of the semiconductor film. In the present disclosure, "does not include one or any "component", "excludes one or any "component", "does not contain a "component", etc. means that the "component" is not added, selected or used as a component in the composition or structure, but due to other impurities and / or external factors, the "component" can still be included in a less than appropriate amount.
[0030] Furthermore, in this specification, the phrase “on a plane” or “plan view” means viewing a target portion from the top, and the phrase “on a cross section” means viewing a cross section formed by vertically cutting the target portion from the side.
[0031] Positive electrode
[0032] A positive electrode for a rechargeable lithium battery according to one or more embodiments includes a dry positive active material layer including a positive active material including large particles of lithium iron phosphate particles and small particles of lithium iron phosphate particles and a polytetrafluoroethylene binder.
[0033] Such a positive electrode refers to a positive electrode prepared by a dry process that does not use (eg, excludes) a solvent in the positive electrode preparation process, as opposed to being prepared by a wet process.
[0034] In one or more embodiments, the positive electrode active material is lithium iron phosphate particles, and includes two types (kinds) of lithium iron phosphate particles having different particle sizes from each other. For example, the positive electrode active material can be large lithium iron phosphate particles and / or small lithium iron phosphate particles.
[0035] In one or more embodiments, the size of the large-particle lithium iron phosphate particles may be larger than the size of the small-particle lithium iron phosphate particles. The size may be an average particle size of the lithium iron phosphate particles, and the average particle size may be an average particle size (D50).
[0036] A positive electrode suitable for a dry cell may be provided as a positive active material comprising large particles of lithium iron phosphate and small particles of lithium iron phosphate. In one or more embodiments, a positive electrode having a relatively high energy density may be obtained or realized. If a positive active material layer is prepared by a wet process using a lithium iron phosphate particle positive active material and a solvent (for example, when a positive active material layer is prepared by a wet process using a lithium iron phosphate particle positive active material and a solvent), the amount of lithium iron phosphate particles that can be coated (for example, a current collector) may be relatively low. As a result, the load level (for example, of the lithium iron phosphate particle positive active material) does not increase or improve, and therefore a positive electrode having a high energy density cannot be obtained. The positive electrode according to one or more embodiments is a dry positive electrode that can improve the load level and can obtain or realize a positive electrode having a high energy density.
[0037] If large-particle lithium iron phosphate particles or small-particle lithium iron phosphate particles are used only (e.g., alone) as a positive electrode active material (e.g., together with a polytetrafluoroethylene binder to prepare a dry positive electrode) (e.g., when large-particle lithium iron phosphate particles or small-particle lithium iron phosphate particles are used only (e.g., alone) as a positive electrode active material (e.g., together with a polytetrafluoroethylene binder to prepare a dry positive electrode)), the adhesion to the current collector may deteriorate. For example, if a positive electrode having a large area is prepared (e.g., when a positive electrode having a large area is prepared), the coating of lithium iron phosphate may be unevenly applied or appear (e.g., on the current collector).
[0038] In one or more embodiments, the mixing ratio of the large-particle lithium iron phosphate particles and the small-particle lithium iron phosphate particles can be a weight ratio of about 99:1 to about 60:40, a weight ratio of about 95:5 to about 65:35, a weight ratio of about 80:20 to about 60:40, or a weight ratio of about 80:20 to about 70:30. If the mixing ratio of the large-particle lithium iron phosphate particles and the small-particle lithium iron phosphate particles is within the corresponding range (for example, when the mixing ratio of the large-particle lithium iron phosphate particles and the small-particle lithium iron phosphate particles is within the corresponding range), the dry positive active material layer can be better prepared, and a positive electrode with a higher energy density can be obtained.
[0039] In one or more embodiments, the ratio of the size of the large-particle lithium iron phosphate particles to the size of the small-particle lithium iron phosphate particles can be about 1.5:1 to about 19:1, about 1.5:1 to about 10:1, or about 2:1 to about 10:1. If the ratio of the size of the large-particle lithium iron phosphate particles to the size of the small-particle lithium iron phosphate particles is within the corresponding range described (for example, when the ratio of the size of the large-particle lithium iron phosphate particles to the size of the small-particle lithium iron phosphate particles is within the corresponding range described), a battery having a suitably high current density (for example, about at least 5 milliampere hours per square centimeter (mAh / cm2)) can be prepared. 2 In some embodiments, if the ratio of the sizes of the two lithium iron phosphate particles is within the corresponding ranges described (for example, when the ratio of the sizes of the two lithium iron phosphate particles is within the corresponding ranges described), a much thicker dry positive electrode can be prepared.
[0040] The large-particle lithium iron phosphate particles may have a size of about 2.5 micrometers (μm) to about 20 μm, about 2.5 μm to about 15 μm, or about 5 μm to about 15 μm.
[0041] The size of the small-particle lithium iron phosphate particles may be about 0.1 μm to about 2.5 μm, about 0.1 μm to about 2 μm, or about 0.5 μm to about 2.0 μm.
[0042] For example, if the ratio of the size of the large-particle lithium iron phosphate particle to the size of the small-particle lithium iron phosphate particle satisfies the corresponding range described (e.g., when the ratio of the size of the large-particle lithium iron phosphate particle to the size of the small-particle lithium iron phosphate particle satisfies the corresponding range described), and if the size (e.g., a single size) of the large-particle lithium iron phosphate particle and the size (e.g., a single size) of the small-particle lithium iron phosphate particle both satisfy the corresponding range described (e.g., when the size (e.g., a single size) of the large-particle lithium iron phosphate particle and the size (e.g., a single size) of the small-particle lithium iron phosphate particle both satisfy the corresponding range described), then the later shear stress can be sufficiently imparted to the binder (i.e., polytetrafluoroethylene binder) used in the preparation of the dry positive electrode. For example, the described sizes and ratios can enable the preparation of a dry positive electrode, wherein a dry positive electrode with a high load level and a high energy density can be obtained. In some embodiments, a dry positive electrode with a high loading level and a high energy density can be obtained even if the lithium iron phosphate positive active material used generally has a low energy density (for example, when the lithium iron phosphate positive active material used generally has a low energy density or despite the fact that the lithium iron phosphate positive active material used generally has a low energy density).
[0043] In one or more embodiments, the large lithium iron phosphate particles and the small lithium iron phosphate particles may be the same as or different from each other. For example, at least one selected from the large lithium iron phosphate particles, the small lithium iron phosphate particles, and a combination thereof may be represented by Chemical Formula 1.
[0044] Chemical formula 1
[0045] Li a Fe 1-x M x PO 4
[0046] Wherein, 0.90≤a≤1.8, 0≤x≤0.7, and wherein M is Mg, Co, Ni, Mn or a combination thereof.
[0047] In the dry positive active material layer according to one or more embodiments, the polytetrafluoroethylene binder may be a fibrillated polytetrafluoroethylene. If shearing is applied (e.g., when shearing is applied), the polytetrafluoroethylene binder may be converted into a fiber shape (e.g., fibrillated) so that the binder is mixed with the positive active material. As a result, the shearing applied thereto may thereby entangle the fibrillated binder and the positive active material to prepare a dry positive active material layer, and a dry positive electrode may be prepared. In the case of using both large-particle lithium iron phosphate particles and small-particle lithium iron phosphate particles of different sizes (e.g., large-particle lithium iron phosphate particles and small-particle lithium iron phosphate particles of different sizes at the same time) as the positive active material, such a dry positive electrode may be prepared. If only small-particle lithium iron phosphate particles are used as the positive active material (e.g., when only small-particle lithium iron phosphate particles are used as the positive active material), it is difficult to prepare a dry positive electrode due to the lack of fibrillation. If only large-particle lithium iron phosphate particles are used as the positive electrode active material (for example, when only large-particle lithium iron phosphate particles are used as the positive electrode active material), it will be difficult to achieve sufficient fibrillation, so that cracks will occur in the particles and one or more side reactions with the electrolyte will occur excessively during charging and discharging.
[0048] In one or more embodiments, the amount of the positive active material may be about 95 wt % to about 99.9 wt %, about 97 wt % to about 99.5 wt %, or about 97.4 wt % to about 99.4 wt % based on 100 wt % of the dry positive active material layer.
[0049] In one or more embodiments, based on a total of 100 wt% of the dry positive active material layer, the amount of the polytetrafluoroethylene binder may be about 0.1 wt% to about 5 wt%, about 0.5 wt% to about 3.0 wt%, or about 0.6 wt% to about 2.6 wt%. If the amount of the polytetrafluoroethylene binder is within the described corresponding range (e.g., when the amount of the polytetrafluoroethylene binder is within the described corresponding range), the dry positive active material layer can be effectively prepared.
[0050] The dry positive active material layer may optionally include a conductive material. In the case where a conductive material is also included in the dry positive active material layer, based on a total of 100wt% of the dry positive active material layer, the amount of the positive active material may be about 90wt% to about 99wt%, about 94wt% to about 99wt%, or about 96wt% to about 99wt%, the amount of the binder may be about 0.5wt% to about 5wt%, about 0.5wt% to about 3wt%, or about 0.5wt% to about 2wt%, and the amount of the conductive material may be about 0.5wt% to about 5wt%, about 0.5wt% to about 3wt%, or 0.5wt% to about 2wt%.
[0051] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof. Carbon black may be, for example, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, or a combination thereof.
[0052] The current collector may be Al, but is not limited thereto.
[0053] The positive electrode according to one or more embodiments may have an energy density of about 400 watt-hours / liter (Wh / L) to about 490Wh / L. In one or more embodiments, the energy density of the positive electrode may be about 400Wh / L to about 450Wh / L, or about 450Wh / L to about 480Wh / L. Thus, the positive electrode according to one or more embodiments may have a high energy density.
[0054] The loading level of the dry positive active material layer can be about 40 mg / cm2 (mg / cm 2 ) to about 90 mg / cm 2 , or about 40 mg / cm 2 About 80mg / cm 2 As such, the dry positive active material layer according to one or more embodiments may have a high loading level.
[0055] In one or more embodiments, the positive electrode may have a current density of at least about 5 mAh / cm2. 2 In one or more embodiments, the current density of the positive electrode can be about 5 mAh / cm 2 to about 8 mAh / cm 2 , or about 6 mAh / cm 2 to about 8 mAh / cm 2 .
[0056] Preparation of positive electrode
[0057] A positive electrode according to one or more embodiments may be prepared as follows (eg, by using a dry mixing process).
[0058] Large particles of lithium iron phosphate particles and small particles of lithium iron phosphate particles are mixed to prepare a positive electrode active material. The positive electrode active material and a polytetrafluoroethylene binder and an optional conductive material are dry mixed, and the resulting mixture is extruded to prepare a dry positive electrode active material layer. A dry mixing process refers to a process that excludes (e.g., does not include) the use of a solvent. The dry mixing process can be performed at a speed of about 1000 rpm to about 10000 rpm, about 1500 rpm to about 8000 rpm, or about 2000 rpm to about 7000 rpm, and can be performed for about 1 minute to about 30 minutes. In the dry mixing process, the polytetrafluoroethylene binder can be fibrillated.
[0059] The dry positive active material layer may be in a sheet type (or type), and may be a self-standing film.
[0060] The dry positive active material layer is adhered to the current collector, thereby preparing a positive electrode. The adhesion process may be a lamination process, but is not limited thereto.
[0061] Rechargeable lithium battery
[0062] A rechargeable lithium battery may include a negative electrode, a positive electrode as described herein, and a non-aqueous electrolyte.
[0063] Negative electrode
[0064] The negative electrode includes a current collector and a negative active material layer on the current collector.
[0065] The negative electrode active material layer includes a negative electrode active material.
[0066] The negative electrode active material includes a material that can reversibly intercalate / deintercalate lithium ions, lithium metal, a lithium metal alloy, a material that can be doped / dedoped with lithium, and / or a transition metal oxide.
[0067] Materials capable of reversibly embedding / desorbing lithium ions can be carbon materials, and for example, can be crystalline carbon, amorphous carbon, or a combination thereof. Crystalline carbon can be natural graphite or artificial graphite of unspecified shape, flaky, lamellar, spherical, or fibrous, and amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0068] Lithium metal alloys include alloys of lithium and at least one metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0069] Materials capable of doping / dedoping lithium can be Si-based anode active materials or Sn-based anode active materials. Si-based anode active materials can be silicon, silicon-carbon (i.e., Si-C) composites, SiO x (0 < x ≤ 2), Si-Q alloys (where Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (except Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or combinations thereof. Sn-based anode active materials can be Sn, SnO 2 , Sn-based alloys, or combinations thereof.
[0070] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to one or more embodiments, the silicon-carbon composite can include silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite can include secondary particles in which silicon primary particles agglomerate and an amorphous carbon coating located on the secondary particles. Amorphous carbon (e.g., also) is located between the silicon primary particles, for example, to coat (e.g., provide a coating) on the silicon primary particles. The secondary particles can be presented by being distributed in the amorphous carbon matrix.
[0071] The silicon-carbon composite can also include crystalline carbon. For example, the silicon-carbon composite can include a core (e.g., secondary particle) containing crystalline carbon and silicon particles (e.g., silicon primary particles) and an amorphous carbon coating on the surface of the core.
[0072] In some embodiments, the silicon particles (e.g., silicon primary particles) can be silicon nanoparticles (e.g., nanoparticles at the nanoscale).
[0073] The particle size of the silicon nanoparticles can be from about 10 nanometers (nm) to about 1000 nm, or according to other embodiments, can be from about 10 nm to about 200 nm, or from about 20 nm to about 150 nm. If the particle size of the silicon nanoparticles is within the corresponding range (e.g., when the particle size of the silicon nanoparticles is within the corresponding range), extreme volume expansion caused during charging and discharging can be suppressed or reduced, and damage to the conduction path due to particle fragmentation can be prevented or reduced.
[0074] In the negative electrode active material according to one or more embodiments, the silicon-carbon composite may include silicon nanoparticles as cores and an amorphous carbon coating on the surface of the silicon nanoparticles. The silicon-carbon composite may include an agglomeration product in which at least one (e.g., two or more) silicon nanoparticles are agglomerated and an amorphous carbon coating on the surface of the agglomeration product.
[0075] In the amorphous carbon coating, the amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbide, sintered coke, or a combination thereof. The thickness of the amorphous carbon coating may be about 1 nm to about 2 μm, about 1 nm to about 500 nm, about 10 nm to about 300 nm, or about 20 nm to about 200 nm. If the thickness of the amorphous carbon coating is within a corresponding range (e.g., when the thickness of the amorphous carbon coating is within a corresponding range), the volume expansion of silicon may be effectively suppressed or reduced during charge and discharge.
[0076] The crystalline carbon may be graphite such as natural graphite or artificial graphite in an unspecified shape, flake, flaky, spherical or fibrous form.
[0077] If the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating (for example, when the silicon-carbon composite includes silicon nanoparticles and an amorphous carbon coating), the amount of the silicon nanoparticles may be about 30 wt % to about 70 wt %, or about 40 wt % to about 65 wt % based on a total of 100 wt % of the silicon-carbon composite. The amount of the amorphous carbon coating may be about 30 wt % to about 70 wt %, or about 35 wt % to about 60 wt % based on a total of 100 wt % of the silicon-carbon composite.
[0078] In the case where crystalline carbon is also included in the silicon-carbon composite, the amount of silicon nanoparticles may be about 20 wt % to about 70 wt %, or about 25 wt % to about 65 wt %, based on a total of 100 wt % of the silicon-carbon composite. The amount of amorphous carbon may be about 25 wt % to about 70 wt %, or about 25 wt % to about 60 wt %, and the amount of crystalline carbon may be about 1 wt % to about 20 wt %, or about 5 wt % to about 15 wt %, based on a total of 100 wt % of the silicon-carbon composite.
[0079] In the negative active material layer, an amount of the negative active material may be about 95 wt % to about 98 wt % based on 100 wt % of the total negative active material layer.
[0080] The negative electrode active material layer may include a binder and may further include a conductive material. The amount of the binder may be about 1 wt % to about 5 wt % based on a total of 100 wt % of the negative electrode active material layer. The amount of the conductive material may be about 1 wt % to about 5 wt % based on a total of 100 wt % of the negative electrode active material layer.
[0081] The binder improves the binding properties between the negative electrode active material particles and between the negative electrode active material particles and the current collector. The binder may include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0082] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0083] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acryloyl resin, phenolic resin, epoxy resin, polyvinyl alcohol or a combination thereof.
[0084] The negative electrode binder may include a cellulose compound, or may include a cellulose compound and an aqueous binder together. Cellulose compounds include one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof. The alkali metal may be Na, K or Li. Cellulose compounds may be used as binders and may be used as thickeners for increasing (e.g., imparting greater) viscosity. The amount of cellulose compounds may be appropriately adjusted within the amount of the binder, but for example, based on 100 parts by weight of the negative electrode active material, the amount may be from about 0.1 parts by weight to about 3 parts by weight.
[0085] The dry binder may be a polymer material that can be in a fibrous form. For example, the dry binder may be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0086] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0087] The current collector may include at least one selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0088] Electrolytes
[0089] In some embodiments, the electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0090] The non-aqueous organic solvent may be or function as a medium for transporting ions that participate (eg, take part in) an electrochemical reaction of a battery.
[0091] The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent or an alcohol solvent, an aprotic solvent or a combination thereof.
[0092] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.), amides such as dimethylformamide, dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.), sulfolane, etc.
[0093] The nonaqueous organic solvents may be used alone or in combination of two or more.
[0094] If a carbonate-based solvent is used (for example, when a carbonate-based solvent is used), a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0095] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, enables basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of the lithium salt include those selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiAlO 2 、LiAlCl 4 、LiPO 2 F 2 、LiCl、LiI、LiN(SO3 C2F 5 ) 2 、Li(FSO 2 ) 2 N(Lithium bis(fluorosulfonyl)imide (LiFSI)), LiC 4 F 9 SO 3 、LiN(C x F2 x+1 SO 2 )(C y F 2y+1 SO 2 )(wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).
[0096] Diaphragm
[0097] Depending on the type or kind of rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof, and a mixed multilayer film such as a polyethylene / polypropylene double-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.
[0098] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof on one or both (eg, opposing) surfaces of the porous substrate.
[0099] The porous substrate can be a polymer film formed by any one selected from the following: polyolefins, such as polyethylene, polypropylene, etc.; polyesters, such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.; polyacetal; polyamide; polyimide; polycarbonate; polyether ketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene oxide; cyclic olefin copolymer; polyphenylene sulfide; glass fiber; Teflon (polytetrafluoroethylene); and copolymers or mixtures of two or more thereof.
[0100] The organic material may include a polyvinylidene fluoride-based polymer or a (meth)acrylic-based polymer.
[0101] The inorganic material may include a 2 O 3 、SiO 2 、TiO 2 SnO 2 、CeO 2 , MgO, NiO, CaO, GaO, ZnO, ZrO 2 , Y2 O 3 、SrTiO 3 、BaTiO 3 Mg(OH) 2 , boehmite and inorganic particles among their combinations, but not limited thereto.
[0102] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer containing an organic material and a coating layer containing an inorganic material may be stacked.
[0103] Rechargeable lithium batteries can be classified into lithium ion batteries, lithium ion polymer batteries or lithium polymer batteries according to the type (kind) of separators and electrolytes used. According to the shape, rechargeable lithium batteries can be classified into cylindrical, prismatic, coin (or class), or pouch (or class). According to the size, rechargeable lithium batteries can be classified into block (or class) or thin film (or class). The structure and manufacture of such batteries are disclosed in the related art, so they will not be described in further detail.
[0104] Rechargeable lithium batteries may be classified into cylindrical, prismatic, pouch-type (or-like) or coin-type (or-like) batteries, etc., according to their shapes. Figures 1 to 4 is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, and Figure 3 and Figure 4 Pouch type (or similar) batteries are shown. Figures 1 to 4 , the rechargeable lithium battery 100 may include an electrode assembly and a case 50 in which the electrode assembly is accommodated, the electrode assembly including a positive electrode 10, a negative electrode 20, and a separator 30 between the positive electrode 10 and the negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown in , the rechargeable lithium battery 100 may include electrode tabs 70 serving as electrical paths for inducing current formed in the electrode assembly 40 to the outside, which may be, for example, a positive electrode tab 71 and a negative electrode tab 72 .
[0105] As a non-limiting example, a rechargeable lithium battery according to one or more embodiments may be applied to automobiles, mobile phones, and / or one or more suitable types (kinds) of electrical devices.
[0106] Terms such as "substantially", "about" and "approximately" are used as relative terms rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that one of ordinary skill in the art would recognize. They may include the stated value and an acceptable range of deviation determined by one of ordinary skill in the art taking into account the limitations and errors associated with the measurement of that amount. For example, "about" may refer to one or more standard deviations, or ±30%, ±20%, ±10%, ±5% of the stated value.
[0107] The numerical ranges disclosed herein include and are intended to disclose all sub-ranges of the same numerical precision. For example, a range of "1.0 to 10.0" includes all sub-ranges having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Therefore, the applicant reserves the right to amend this specification and claims to explicitly recite any sub-ranges contained within the ranges explicitly recited herein.
[0108] The following examples and comparative examples are provided to highlight the features of one or more embodiments, but it will be understood that the examples and comparative examples should not be interpreted as limiting the scope of the embodiments, and the comparative examples should not be interpreted as being outside the scope of the embodiments. In addition, it will be understood that the embodiments are not limited to the specific details described in the examples and comparative examples.
[0109] Example
[0110] Example 1
[0111] The average particle size D50 of LiFePO is 5 microns (μm) 4 LiFePO particles with an average particle size D50 of 0.5 μm 4 The particles were mixed in a weight ratio of 6:4 to prepare a positive electrode active material.
[0112] 90 wt % of the positive active material, 5 wt % of the polytetrafluoroethylene binder and 5 wt % of the Ketjen black conductive material were dry mixed at 5000 rpm for 10 minutes, and the mixture was extruded to prepare a sheet-type (or similar) self-standing film dry positive active material layer.
[0113] The dry positive active material layer was laminated on an Al foil current collector to prepare a positive electrode. In the prepared positive electrode, the dry positive active material layer had a carbon content of 40 mg / cm2. 2 ) loading level, and the polytetrafluoroethylene binder is fibrillated polytetrafluoroethylene.
[0114] 98 wt% of natural graphite negative active material, 1 wt% of styrene butadiene rubber and 1 wt% of carboxymethyl cellulose were mixed in an aqueous solvent to prepare a negative active material layer slurry. The negative active material layer slurry was coated on a Cu foil current collector, dried and pressed to prepare a negative electrode.
[0115] A full battery with a volume of 0.96 L was fabricated using the positive electrode, negative electrode, and electrolyte. 6 The electrolyte was used by dissolving in a mixture of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate (2:1:7 volume ratio) to prepare a mixed solvent and adding 3.5 wt % of fluoroethylene carbonate based on the total weight of the mixed solvent to the mixed solvent.
[0116] Example 2
[0117] In addition to the large particles of LiFePO with an average particle size D50 of 5 μm 4 LiFePO particles with an average particle size D50 of 0.5 μm 4 A positive electrode and a full cell having a volume of 0.96 L were manufactured by the same steps as in Example 1 except that the particles were mixed in a weight ratio of 65:35. In the prepared positive electrode, the dry positive active material layer had a carbon content of 60 mg / cm 2 The loading level is 0.0447 W, and the polytetrafluoroethylene binder is fibrillated polytetrafluoroethylene.
[0118] Example 3
[0119] In addition to using large particles of LiFePO with an average particle size D50 of 10 μm 4 LiFePO particles with an average particle size D50 of 1 μm 4 Except for the particles, a positive electrode and a full cell with a volume of 0.96 L were manufactured by the same steps as in Example 1. In the prepared positive electrode, the dry positive active material layer had a carbon content of 70 mg / cm 2 The loading level is 0.0447 W, and the polytetrafluoroethylene binder is fibrillated polytetrafluoroethylene.
[0120] Example 4
[0121] In addition to using large particles of LiFePO with an average particle size D50 of 10 μm 4 LiFePO particles with an average particle size D50 of 2.0 μm 4 Except for the particles, a positive electrode and a full cell with a volume of 0.96 L were manufactured by the same steps as in Example 1. In the prepared positive electrode, the dry positive active material layer had a carbon content of 80 mg / cm 2 The loading level is 0.0447 W, and the polytetrafluoroethylene binder is fibrillated polytetrafluoroethylene.
[0122] Comparative Example 1
[0123] The average particle size D50 of LiFePO is 5 μm. 4 LiFePO particles with an average particle size D50 of 0.5 μm 4 The particles were mixed in a weight ratio of 60:40 to prepare a positive electrode active material.
[0124] 98 wt % of a positive electrode active material, 1 wt % of a polytetrafluoroethylene binder, and 1 wt % of a Ketjen black conductive material were mixed in an N-methylpyrrolidone solvent to prepare a positive electrode active material layer slurry.
[0125] The positive electrode active material layer was laminated on an Al foil current collector to prepare a positive electrode. In the prepared positive electrode, the positive electrode active material layer had a carbon content of 30 mg / cm 2 load level.
[0126] A full (battery) having a volume of 0.96 L was manufactured by the same steps as in Example 1 using the positive electrode.
[0127] Comparative Example 2
[0128] In addition to using large particles of LiFePO with an average particle size D50 of 20 μm 4 LiFePO particles with an average particle size D50 of 2.5 μm 4 A positive electrode and a full cell with a volume of 0.96 L were manufactured by the same steps as those in Comparative Example 1 except that the particles were prepared and polyvinylidene fluoride binder was used instead of polytetrafluoroethylene binder. In the prepared positive electrode, the positive active material layer had a positive electrode content of 35 mg / cm 2 load level.
[0129] Comparison Example 3
[0130] In addition to using only large particles of LiFePO with an average particle size D50 of 30 μm 4 A positive electrode and a full cell with a volume of 0.96 L were manufactured by the same steps as those of Example 1, except that the particles were used as the positive electrode active material. In the prepared positive electrode, the positive electrode active material layer had a carbon content of 38 mg / cm 2 load level.
[0131] Comparison Example 4
[0132] In addition to using only small particles of LiFePO with an average particle size D50 of 0.05 μm 4A positive electrode and a full battery with a volume of 0.96 L were manufactured by the same steps as those of Example 1, except that the positive electrode active material layer had a positive electrode active material layer of 25 mg / cm 2 load level.
[0133] Experimental Example 1 - Current Density (mAh / cm 2 )'s review
[0134] The current density of the positive electrodes according to Examples 1 to 4 and Comparative Examples 1 to 4 was calculated by Equation 1. For example, if the current density of Example 1 is calculated by Equation 1 (for example, when the current density of Example 1 is calculated by Equation 1), it is 40 (mg / cm2 (mg / cm 2 ))×90(%)×140(milliampere-hour / gram (mAh / g))=5(milliampere-hour / square centimeter (mAh / cm 2 )).
[0135] Equation 1
[0136] Current density = loading level (mg / cm 2 )×active material ratio (%)×capacity of LFP (mAh / g)
[0137] In equation 1, the capacity of LFP is LiFePO 4 The experimental capacity is 140 mAh / g.
[0138] Experimental Example 2-Evaluation of Energy Density (Wh / L)
[0139] The energy density of the half-cells according to Examples 1 to 4 and Comparative Examples 1 to 4 was calculated by Equation 2. The results are shown in Table 1. For example, if the energy density of Example 1 is calculated by Equation 2 (for example, when the energy density of Example 1 is calculated by Equation 2), it is 3.2 (V) × 135 (ampere-hour (Ah)) / 0.96 (L) = 450 (watt-hour / liter (Wh / L)).
[0140] Equation 2
[0141] Energy density (Wh / L) = theoretical voltage (nominal voltage, V) × battery capacity (Ah) / battery volume (L)
[0142] In Equation 2, the battery capacity is obtained from the current density obtained by Example 1.
[0143] Table 1
[0144]
[0145] As shown in Table 1, in Examples 1 to 4, the 2 or higher loading level of the positive electrode, therefore, the current density of the positive electrode is 5 mAh / cm 2 As a result, a positive electrode having a high energy density of 450Wh / L or more can be prepared, and as a result, a battery having a high capacity of 135Ah or more can be prepared.
[0146] The positive electrodes of Comparative Examples 1 and 2, both prepared by the wet process, showed a value of 30 mg / cm 2 and 35mg / cm 2 of low load levels, and as a result, they exhibit each of (e.g., all) low current density, low energy density, and low battery capacity.
[0147] Only large particles of LiFePO are used 4 Comparative Example 3 of particle preparation shows 38 mg / cm even when the positive electrode is prepared by a dry process (for example, when the positive electrode is prepared by a dry process). 2 The slightly increased load level of Example 1 to Example 4 is still lower than the load level of Example 1 to Example 4. Therefore, the current density, energy density and battery capacity are all lower than those of Example 1 to Example 4. 4 In Comparative Example 4 of particle preparation, the positive electrode has a particle size of 25 mg / cm 2 The extremely low load levels of , therefore the current density, energy density and battery capacity are (eg, all) significantly low.
[0148] Any suitable hardware, firmware (e.g., an application specific integrated circuit), software, or a combination of software, firmware, and hardware may be used to implement a battery management system (BMS) device and / or any other related device or component according to an embodiment of the present disclosure described herein. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on separate IC chips. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads that execute computer program instructions and interact with other system components for performing the various functions described herein, running on one or more processors in one or more computing devices. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device (such as a random access memory (RAM) as an example). The computer program instructions may also be stored in other non-temporary computer-readable media (such as a CD-ROM, a flash drive, etc. as an example). In addition, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a particular computing device may be distributed across one or more other computing devices.
[0149] Although the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it will be understood that the present disclosure is not limited to the disclosed embodiments, but on the contrary, is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents. Therefore, the foregoing embodiments should be understood as examples, and not to limit the present disclosure in any way.
[0150] <Description of Reference Signs>
[0151] 100: Rechargeable lithium battery 10: Positive electrode
[0152] 11: Positive electrode lead tab 12: Positive terminal
[0153] 20: Negative electrode 21: Negative electrode lead lug
[0154] 22: Negative terminal 30: Separator
[0155] 40: electrode assembly 50: shell
[0156] 60: Sealing member 70: Electrode terminal piece
[0157] 71: positive electrode terminal tab 72: negative electrode terminal tab.
Claims
1. A positive electrode, comprising: The dry positive electrode active material layer comprises: a positive electrode active material, including large lithium iron phosphate particles and small lithium iron phosphate particles; and a polytetrafluoroethylene binder, Wherein, the positive electrode is used in a rechargeable lithium battery.
2. The positive electrode according to claim 1, wherein The mixing ratio of the large lithium iron phosphate particles to the small lithium iron phosphate particles is 99:1 to 60:40 by weight.
3. The positive electrode according to claim 1, wherein The large lithium iron phosphate particles have a size greater than that of the small lithium iron phosphate particles.
4. The positive electrode according to claim 3, wherein The ratio of the size of the large lithium iron phosphate particles to the size of the small lithium iron phosphate particles is 1.5:1 to 19:
1.
5. The positive electrode according to claim 3, wherein The large lithium iron phosphate particles have a size of 2.5 μm to 20 μm.
6. The positive electrode according to claim 3, wherein The size of the small lithium iron phosphate particles is 0.1 μm to 2.5 μm.
7. The positive electrode according to claim 1, wherein The polytetrafluoroethylene binder includes fibrillated polytetrafluoroethylene.
8. The positive electrode according to claim 1, wherein The large lithium iron phosphate particles and the small lithium iron phosphate particles are the same or different, and at least one selected from the large lithium iron phosphate particles, the small lithium iron phosphate particles, and a combination thereof is represented by Chemical Formula 1: [Chemical formula 1] Li a Fe 1-x M x PO4, and Where 0.90≤a≤1.8, 0≤x≤0.7, and M is Mg, Co, Ni, Mn or a combination thereof.
9. The positive electrode according to claim 1, wherein The amount of the polytetrafluoroethylene binder is 0.1 wt % to 5.0 wt % based on 100 wt % of the dry positive active material layer.
10. The positive electrode according to claim 1, wherein The dry positive electrode active material layer further includes a conductive material.
11. The positive electrode according to claim 1, wherein The positive electrode has an energy density of 400 Wh / L to 490 Wh / L.
12. The positive electrode according to claim 1, wherein The dry positive electrode active material layer has a 40 mg / cm 2 Up to 90mg / cm 2 load level.
13. The positive electrode according to claim 1, wherein The positive electrode has a capacity of at least 5 mAh / cm 2 of current density.
14. The positive electrode according to claim 1, wherein The positive electrode has a 5 mAh / cm 2 Up to 8mAh / cm 2 of current density.
15. A rechargeable lithium battery, the rechargeable lithium battery include : The positive electrode according to any one of claims 1 to 14; a negative electrode; and Non-aqueous electrolytes.